Running wild eaudiobook - Andersen, Susan (Sisterhood Diaries, 2016)
Magdalene Deluca isn't the damsel-in-distress type. But if she has to involve a stranger in a dangerous chase through South America, she's glad Finn Kavanagh's the guy she sucked into her problems. Very glad. The man oozes sex and magnetic confidence. And since their connection is steamier than the sultry rain forest, why waste time resisting him? Finn's peaceful vacation is blown to bits the second Mags strides into view. For years he's ignored his family's pleas to settle down. Now he's falling hard for a blonde force of nature who's allergic to commitment. First he has to keep Mags safe as they search for her missing parents. Then they can determine if it's time to stop running, and take a chance on the wildest thrill they've ever known . . . Contains mature themes.